The Relationship Between Ecotourism Awareness and Ecotourism Perception - Ercan İştin, Aysen; Bakır, Vildan (Muş Alparslan Üniversitesi, 2021)
Araştırma için etik kurul onayı Şırnak Üniversitesi Etik Kurulu'ndan 09.04.2021 (No:2021/32) tarihinde alınmıştır. Araştırmanın temel amacı, Şırnak ilinde yaşayan halkın ekoturizm farkındalığı ve ekoturizm algısı arasındaki ilişkiyi incelemektir. Bu kapsamda nicel araştırma yöntemi kullanılarak 10 Nisan-30 Mayıs 2021 tarihleri arasında anket ile veriler toplanmıştır. Veriler WhatsApp, Facebook, e-posta ve yüz yüze görüşmeler yoluyla toplanmıştır. Araştırmanın evrenini 18 yaş üstü yerel halk ile Şırnak ilinde en az 5 yıl ikamet eden kişiler oluşturmaktadır. Araştırmanın örneklemi evreni temsil eden araştırmaya katılan Şırnak ilinde yaşayan (421 katılımcı) kişilerdir. Analizler sonucunda, ekoturizmin anlamına ilişkin farkındalık ile ekoturizm algısı arasında yüksek düzeyde pozitif doğrusal bir ilişki olduğu tespit edilmiştir. Ayrıca, ekoturizmin anlamına ilişkin farkındalık ile uygulanabilir ekoturizm faaliyetlerine ilişkin farkındalık arasında ve uygulanabilir ekoturizm faaliyetlerine yönelik farkındalık ile ekoturizm algısı arasında düşük düzeyde pozitif doğrusal bir ilişki olduğu tespit edilmiştir. Regresyon analizi sonuçlarının da bu sonuçları desteklediği belirlenmiştir.

Ethics committee approval was obtained for the research from the Ethics Committee of Sirnak University on 09.04.2021 (No:2021/32). The main purpose of the research is to examine the relationship between people's ecotourism awareness and their ecotourism perception, who living in Şırnak province. In this context, data were collected by questionnaire between April 10 and May 30, 2021 using the quantitative research method. Data were collected through WhatsApp, Facebook, e-mail, and face-to-face interviews. The population of the research consists of local people and people residing in Şırnak province for at least 5 years over the age of 18. The sample of the research is people living in Şırnak province (421 participants) who participated in the research representing the universe. As a result of the analysis, it was determined that there is a high-level positive linear relationship between awareness regarding meaning of ecotourism with ecotourism perception. In addition, it was determined that there is a low level of the positive linear relationship between awareness regarding meaning of ecotourism with awareness regarding applicable ecotourism activities, and between awareness regarding applicable ecotourism activities with ecotourism perception. Also, it was determined that the results of the regression analysis also supported these results.
Ecoturizm Farkındalığı ve Ecoturizm Algısı Arasındaki İlişki
anemon
Keywords: Ekoturizm; Ekoturizm farkındalığı; Ekoturizm algısı; Şırnak; Türkiye; ecotourism; ecotourism awareness; ecotourism perception; Sirnak; Turkey